Evaluation of the fit of preformed nickel titanium arch wires on normal occlusion dental arches - Rakhn G. Al-Barakati; Nasser D. Alqahtani; Abdulaziz AlMadi; Sahar F. Albarakati; Eman A. ALKofide (Saudi Dental Journal)
Aim: To determine the fits of preformed nickel titanium (NiTi) archwires on dental arches with normal occlusion. Methods: Forty sets of upper and lower plaster models were obtained from men and women with Class I occlusions. Preformed 0.016″ × 0.022″ NiTi archwires from Rocky Mountain Orthodontics (RMO), 3 M Unitek, Ormco, and Dentaurum were evaluated in terms of their fits on dental arches from male, female, and combined cases. Data were analyzed by using fourth- and sixth-order polynomial equations, analysis of variance (ANOVA), and the Duncan post hoc test. Results: In the upper arches, the best fit and least error were obtained with RMO Ovoid and Ormco Orthos Large archwires for male cases, but with 3 M Orthoform LA archwires for female and combined cases. In the lower arches, the best fit and least error were obtained with Ormco Orthos Large for male cases, with 3 M Orthoform LA and RMO Normal for female cases, and with 3 M Orthoform LA, RMO Normal, Ormco Orthos Large, and Ormco Orthos Small for combined cases. When both dental arches were matched, Ormco Orthos Large was the best wire for male cases. 3 M Orthoform LA was the best wire for female and combined cases. Conclusions: Using an archwire form with the best fit to the dental arch should produce minimal changes in the dental arch form when NiTi wires are used and require less customization when stainless-steel wires are used. Keywords: Nickel titanium, Arch wires, Occlusion